Development of Nationwide Surface Spectral Acceleration Maps for Earthquake Resistant Design of Bridges Based on National Hazard Maps of Indonesia 2017 - Reguel Mikhail; Masyhur Irsyam; Ramli Nazir; Mohammad Asrurifak; Bigman Marihat Hutapea; Siska Rustiani; Munirwansyah Munirwansyah; Dandung Sri Harninto (Journal of Engineering and Technological Sciences, 2019)
Spectral acceleration at the ground surface, including peak ground acceleration, provides essential information for earthquake resistant design and must be provided to bridge engineers in easily accessible media. Spectra acceleration maps are one way to deliver such information, but unfortunately the most recent Indonesian earthquake resistant design standard for bridges, SNI 2833-2016, only provides maps of earthquake hazard at bedrock. The development of earthquake acceleration maps at the ground surface for Indonesia in this study was based on earthquake hazard maps at bedrock with probability of exceedance (PE) 7% in 75 years, i.e. equal to an earthquake with a return period of 1034 years. Site conditions were adopted from the nationwide Vs30 map of Indonesia proposed by Irsyam (2017), which is a modified version of the Vs30 map proposed by Imamura & Furuta (2015). Site conditions combined with hazard value were used to determine the amplification factors according to the criteria in SNI 2833-2016 and then multiplied with hazard at bedrock to obtain surface spectra acceleration maps. The resulting maps are very useful for determining earthquake loads for bridge design at the preliminary design stage. Improvements to incorporate more advanced calculation methods and updated data in a future research are recommended and very feasible.